Improving The English Skills Of Elementary School Students Using The Phonetic Method - Lestari, Dewi (Prosiding University Research Colloquium, 2021)
This research was conducted using a qualitative descriptive method. The study aims to know the effectiveness of phonetic methods in improving the English skills of elementary school students. Language plays a very important role in our daily lives, to communicate ideas to others. Language skils are the basic ingredients for everyone to express themselves starting from the feelings, desires, opinions, and needs of each individual. The more language a person knows, the easier it is for him to communicate. Understanding English must be solidified to students as an international language. The study was based in the thought that students should be speaking English in daily interactions in the school language program. Because of this, the need to learning pronunciation, vocabulary and grammar in English learning is essential for improving students language skills, students should study the pronunciation, vocabulary, and grammar as much as possible to establish good communication with other students.